Biodegradation and migration behavior of cellulose nanocrystal - nanoclay reinforced PLA composites - Behzad Kord (Regional Information Center for Science and Technology (RICeST), 2016)
In this study, the synergic effects of cellulose nanocrystal and nanoclay on the biodegradation and migration behavior of composite films based on polylactic acid (PLA) were investigated.  PLA and PLA-based nanocomposite ﬁlms containing different loads of cellulose nanocrystal and nanoclay (0, 3 and 5 wt % each) were fabricated using a solvent casting method. In order to improve the compatibility and miscibility of the whole system with respect to PLA matrix, cellulose nanocrystal was treated with oleic acid. For evaluating the biodegradation and migration behavior of films, the enzymatic degradation, biodegradation, buried in soil and compost; and overall migration were tested. The results indicated that the biodegradability of the composites increased with the increase of nanoparticles in the enzymatic, soil and compost media. Besides, with the addition of cellulose nanocrystal and nanoclay to the polymer matrix, the overall migration of composites decreased. This  could  be  due  to  a  better  adhesion  of  the  nanoparticles  to  the  polymer  matrix,  and the  tortuousity of  their  path.